Molecular and Biochemical Characterization of a Type II Thioesterase From the Zoonotic Protozoan Parasite Cryptosporidium parvum - Guo, Fengguang; Zhang, Haili; Eltahan, Rana; Zhu, Guan (Frontiers in Cellular and Infection Microbiology, 2019)
Cryptosporidium parvum is a globally important zoonotic parasite capable of causing severe to deadly diarrhea in humans and animals. Its small genome (~9.1 Mb) encodes not only a highly streamlined metabolism, but also a 25-kb, 3-module fatty acid synthase (CpFAS1) and a 40-kb, 7-module polyketide synthase (CpPKS1). The two megasynthases contain a C-terminal reductase domain to release the final products with predicted chain lengths of ≥C22 for CpFAS1 or C28 to C38 for CpPKS1.The parasite genome also encodes a discrete thioesterase ortholog, suggesting its role to be an alternative tool in releasing the final products from CpFAS1 and/or CpPKS1, or as an editor to remove non-reactive residues or aberrant intermediates, or to control starter units as seen in other parasites. In this study, we have confirmed that this C. parvum thioesterase is a type II thioesterase (thus named as CpTEII). CpTEII contains motifs and a catalytic triad characteristic to the type II thioesterase family. CpTEII is expressed during the entire parasite life cycle stages with the highest levels of expression in the later developmental stages. CpTEII showed the highest hydrolytic activity toward C10:0 decanoyl-CoA, so we speculated that CpTEII may mainly act as an editor to remove non-reactive residues and/or aberrant medium acyl chain from CpFAS1 and/or CpPKS1. However, we cannot rule out the possibility that CpTEII may also participate in the release of final products from CpFAS1 because of its moderate activity on C20:0, C:22:0 and C24:0 acyl-CoA thioesters (i.e., ~20–30% activity vs. decanoyl-CoA).